Nilai Pendidikan Karakter dan Pesan Edukatif dalam Dongeng Nusantara Bertutur - Latifah, Suci Ayu; Sutejo, Sutejo; Suprayitno, Edy (Jurnal Bahasa dan Sastra, 2021)
The story of Nusantara Bertutur Kompas is one of children’s literary works. Through the characters, the author inserts values and story messages to enlighten life. Therefore, this study aimed to describe the value of character education and educative messages within the children’s story. The research used descriptive qualitative method, designed as literary study. It was done by finding descriptive data in the form of quotes, statements, and narration. Data collection techniques were note-taking and then analyzed by using the following steps; data identification, classification, reduction, and conclusion. The results of the analysis showed there were 15 out of 18 values of character education and 15 educational messages spread in each story. The fifteen educational characters involved religious, honest, tolerant, disciplined, hard work, creative, independent, democratic, curiosity, love for the homeland, respect for achievement, friendship, love peace, social care and responsibility. Educational messages found were children’s fairy tales which associated with the value of character education and the realities in everyday life. Suggestion for all readers who wish to compile research on the similar topic, may need to conduct more thorough, careful, and accurate research. So, they can produce a comprehensive and deeper research.